Use of YouTube for Diffusion of Innovative Agricultural Technologies: A Digital Self-Help Approach to the Farmers - Mazumder, Mohummed Shofi Ullah; Wadud, Fatema; Barua, Sushama (Journal of Agricultural Sciences (Belgrade), 2026)
The diffusion of innovative agricultural technologies is essential for improving productivity, food security, and rural livelihoods in developing countries, where conventional extension services often face financial and institutional constraints. This study investigates the role of YouTube as a digital self-help platform for farmers in rural Bangladesh, emphasising its effectiveness in disseminating agricultural information and the factors influencing its adoption. A cross-sectional survey of 276 farmers was conducted in Rangunia Upazila (sub-district) under the Chattogram district. Data was collected using a structured questionnaire and analysed using regression analysis. After considering Variance Inflation Factor (VIF) value, multivariate logistic regression was conducted. The results show that YouTube adoption is significantly associated with education, effective farm size, and agricultural extension contact. Farmers using YouTube reported higher agricultural knowledge, greater incomes, and more diversified farming practices than non-users. Additionally, YouTube was widely used for weather forecasts, disaster preparedness, peer learning, post-harvest management, and market engagement, underscoring its multifunctional role. Overall, platforms such as YouTube, when supported by improved ICT access, affordable digital resources, and targeted training, can significantly enhance agricultural knowledge and technology adoption among Bangladeshi farmers, thereby promoting sustainable rural development.